2021
DOI: 10.1039/d1ra05810j
|View full text |Cite
|
Sign up to set email alerts
|

On the diatomite-based nanostructure-preserving material synthesis for energy applications

Abstract: The present article overviews the current state-of-the-art and future prospects for the use of diatomaceous earth (DE) in the continuously expanding sector of energy science and technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 291 publications
(604 reference statements)
1
12
0
Order By: Relevance
“…The utilization of diatomite meneral as a substrate combines the advantage of both CNTs and diatomite. According to previous investigations [23], we suggest that obtained Sample 2 (Diatomite/CNT) is highly crystallized, retains the porous structure of diatomite and contains fewer impurities, therefore the specific surface area increased in comparison pure diatomite, Sample 1 (Table 1).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The utilization of diatomite meneral as a substrate combines the advantage of both CNTs and diatomite. According to previous investigations [23], we suggest that obtained Sample 2 (Diatomite/CNT) is highly crystallized, retains the porous structure of diatomite and contains fewer impurities, therefore the specific surface area increased in comparison pure diatomite, Sample 1 (Table 1).…”
Section: Resultssupporting
confidence: 56%
“…This area is well explored, continues to be explored, and remains a potential game changer in battery technology. It is known that the theoretical capacity of silicon is higher than graphite [1].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Figure 3 , it can be observed that the surface of the raw HDPE is smooth, in contrast to the surface of the injection mold containing the DE/ZnO composite, which has a rough surface. Additionally, one can observe aggregate elements all over the surface, which corresponds to the DE/ZnO composite, and the EDS results show that Zn and Si elements are well dispersed all over the surface of the test specimen [ 36 , 37 ]. Regarding thermal stability, Figure 4 shows the TGA and its first derivative (DTG) curves.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] The advances made using diatomite as a source of silica, silicon-based materials, and templates for energy-related applications are provided in the latest review article. 29 Through the functionalization of diatomite, its properties and range of applications can be further upgraded and expanded. Some of the most widely used functionalization approaches include noncovalent and covalent functionalization and chemical conversion of diatomite.…”
Section: Introductionmentioning
confidence: 99%